Cálculos de primeiros princípios das propriedades eletrônicas e vibracionais de nanotubos de carbono funcionalizados ou sobre strain - Carneiro, Marciano Alves (2009)
The goal of this thesis is the study of the structural, electronic and vibrational properties of single wall carbon nanotubes (SWNTs) under different conditions, such as covalently functionalized nanotubes, nanotubes encapsulating molecules and nanotubes under tension or compression. To determine the nanotubes properties, we use a computational fisrt principles approach, based on the Density Functional Theory (DFT), as implemented in the SIESTA code (Spanish Initiative for Electronic Simulations with Thousands of Atoms), with the local density and generalized gradient approximations for the exchange-correlation terms. Electrons-ions interactions are described by the pseudopotential approximation. For covalently functionalized nanotubes we investigated the electronic and energetic properties of metallics nanotubes SWNT (5,5) interacting with radicals of an aminoacid, the alanine. We show that when the alanine is most hardly bound to the nanotube all atoms in the nanotubo preserve their sp2 hibridization, keeping the characteristic of a -electrons system and its metallic behaviour. We also studied different quiralities carbon nanotubes encapsulating linear carbon molecules, the polyynes. We calculated the electronic and vibrational properties of isolated and encapsulated polyynes. We see that when encapsulated, the polyynes always present a downshift in their vibrational frequencies, while for large diameter nanotubes the changes in the vibrational frequencies are not significant. Concernig carbon nanotubes under tension and compression, we analized the structural, electronic and vibrational properties changes. We show that strain leads to modifications of the vibrational properties of the nanotubes. The frequencies of the G band and the radial breatinhg mode (RBM) band increase monotonically with strain. Besides, we identify sctructural transitions for critical compressions that affect significantly mostly the RBM frequencies and also sometimes the G band frequencies. We also report the modifications in the nanotubes energy gaps as a function of strain.